Integrating Industrial Internet of Things and Cyber-Physical Systems: A Comprehensive Overview in Smart City Scenarios - Fadhil, Ali Muayed (Basrah Journal for Engineering Sciences, 2025)
The Internet of Things (IoT) connects everyday objects to the Internet by integrating a vast network of interconnected smart devices into residential and commercial settings. When the Industrial Internet of Things (IIoT) changed how industries work by connecting and communicating devices and systems in industrial environments, these devices linked to the Internet gathered information from their surroundings, processed it, and sent it safely. Industry 4.0 transforms transportation and manufacturing industries by producing smart devices for total automation. This system has a substantial application in predictive maintenance. Predicting disasters in dangerous areas aids in managing safety and decreasing damage. In this paper, presented review for the integration of Cyber-Physical Systems (CPS) and IIoT in smart cities is fundamentally transforming urban services and infrastructure. Smart cities leverage technology to enhance inhabitants' quality of life, foster sustainability, and streamline municipal governance. Artificial intelligence is applied with IIoT's production and analysis data to generate speedier outcomes. The article discusses IIoT uses, supporting technologies, growth issues and how to fix them, and suggestions for growth and better performance by limitless potential, including better manufacturing, greener electricity production, self-regulating structures, and smart cities that can modify traffic patterns to reduce congestion.